Encounter of Asiatic Black Bear (Ursus thibetanus) from the Low Elevated Area of District Battagram, Pakistan - Zaib Ullah; Usama (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Asiatic black bear (Ursus thibetanus) is widely distributed in various countries of Asia including different areas of Pakistan such as District Mansehra, Swat, Kohistan, Battagram, Gilgit Baltistan, and Azad Jammu and Kashmir. The present research was conducted in District Battagram, Khyber Pakhtunkhwa, Pakistan where new and abundant evidence of the Asiatic Black bear was reported. Data were collected during field reports, questionnaire-based surveys and oral interviews, and discussions with the local community from March 2022 to December 2022. The black bear was encountered by local peoples at a low elevated area (1259 m) of Jesol village (N 34o 41' 53" E 73o 03' 05") and was killed collectively (May 12, 2022). During such an encounter, a young man was also injured in conflict. Within one day, local people carried every part of the bear’s body and left the remaining skeleton. The wildlife department of Khyber Pakhtunkhwa took immediate action against the involved people. Similarly, the second black bear was also observed in the same village after one week but this time local people did not take any action against the black bear due to strict enforcement of wildlife law implemented by the wildlife department. On the other hand, questionnaire-based surveys and oral interviews were conducted in different areas of Battagram such as Baliga, Chail, and Shumlai about the black bear population. According to the perception of the local community, a quite good population of bears n=14 (6 males, 4 females, and 4 cubs) are present in the entire district. During the field survey, bear signs were also observed in Balija Mountain such as pug marks, track routing in snow, scat samples, and setting place. Bone samples collected from a killed black bear will be genetically identified for further genotypic study. The black bear population could be conserved by the strict implementation of rules and regulations by the government and conservation agencies. Awareness among the local community also plays an important in black bear conservation.